Laporan Kasus : Wanita 36 Tahun Diduga Dengan Inkompetensi Serviks Di Prof. Rumah Sakit W.Z. Johannes, Kupang, Nusa Tenggara Timur, Indonesia - Putera, Dewa Gede Agung Sasmara; Tokan, Lambertus Bambang (Cendana Medical Journal, 2023)
Cervical incompetence is the inability of the cervix to maintain a pregnancy due to functional or structural defects in the cervix. Transvaginal ultrasound examination is the gold standard for determining an incompetent cervix. The patient is a 36-year-old woman with a history of 6 preterm births with no known cause. The patient first came with preterm labor but was sent home and 2 days later came back to the emergency room after spontaneous delivery at home. Supportive treatment such as cerclage sutures can prevent infection and can maintain gestation to term to prevent the dangers of preterm labor.